Education quality and readability improvement efforts in primary public schools in Egypt: A process analysis - Abou Hegab, Mays (AUC Knowledge Fountain, 2017)
This research aims at investigating the challenges of achieving education quality in public primary schools in Egypt, with a specific focus on readability issues. The researcher employed a qualitative approach to research, using semi-structured face-to-face interviews. The main findings of the research suggested that the main reasons affecting the efficiency of the education quality efforts and thus reading and writing proficiency in public primary schools include: (1) poor school resources including oversized classes and poor quality of teachers; (2) enhanced readability curricula and assessments are not in use, especially for restorative programs; (3) contradicting laws and regulations, such as the decree on automatic transfer of students; (4) lack of coordination between the different entities mandated with achieving education quality; among others. Recommendations include increasing the public funding of the education sector to cover education quality interventions from the state budget; enforcing the use of the readability curricula and the EGRA assessment tools; as well as adopting pro-poor policies in poor communities.